An identification approach to the problem of discrete-time dynamical plant under irregular disturbance - Азарсков, В.М.; Житецький, Л.С.; Сущенко, О.А. (Proceedings of National Aviation University (archive), 2004)
The closed-loop system for the stabilization of discrete-time minimum phase plant under irregular unmeasurable disturbance is designed. It contains an usual PID controller and adaptive controller using the current estimates of unknown plant parameters. To decrease the stabilization error during at initial adaptation stage, the autonomous identification regime is introduced. The rule of controllers switching is formulated.